(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This study investigates the performance of pressure differential Wave Energy Converters (WECs) to support deployment as a cluster on a versatile floating platform, with a focus on stand-alone configurations and potential hybrid applications in the floating offshore wind sector. Extending research from the Wave Energy Scotland’s (WES) Multi Wave Absorber Platform (MWAP) project, the study investigates the use of a frequency domain model and explores avenues for model refinement using experimental data. The frequency domain model incorporates hydrodynamic characteristics, such as excitation forces, added mass, and radiation damping, estimated using WAMIT. In this paper, the validity of the underlying assumptions of this model, the hydrodynamic characteristics used to define it and predictions made with it are assessed with reference to experimental data. Experimental data used for this purpose includes reaction forces from load cells and observations of hydrodynamic effects using flow visualisation techniques. Experiments were conducted at the FloWave Ocean Energy Research Facility using a scaled triangular platform fitted with nine identical pressure differential WECs. Velocity fields were captured with a particle tracking velocimetry system to characterise hydrodynamic behaviour. While these observations provided qualitative insights into flow patterns, load cell measurements were more directly utilised for exploring absorber hydrodynamics and refining model parameters. Initial comparison between numerical predictions and tank test data for static WECs (without additional spring and damping) indicate that the WAMIT MWAP models effectively capture general system response trends. However, discrepancies highlight the need for model refinements, such as transitioning to time-domain models to incorporate non-linear forces like viscous damping and higher-order effects. These refinements are expected to improve alignment with experimental results and provide a more accurate representation of absorber and platform dynamics. This research demonstrates the value of combining experimental and numerical approaches to improve the design and deployment of pressure differential WECs on floating platforms. It provides a foundation for optimising absorber spacing, platform configurations, and other design parameters while addressing the challenges of scaling and cost-effective deployment in stand-alone or hybrid configurations.